Influence of vitamin E on the levels of fatty acids and MDA in some tissues of diabetic rats - Çelik, S; Baydas, G; Yilmaz, Ö (Wiley, 2002)
This study was performed to determine whether vitamin E supplementation in streptozotocin-induced diabetic rats treated with insulin could affect the levels of fatty acid composition and malondialdehyde (MDA) of brain, liver and muscle tissues. Thirty Wistar albino rats were used during the experiments. They were randomly divided into three groups, each consisting of six individuals. The first group was diabetic, the second was control, and the third was diabetic but fed vitamin E. The level of stearic acid in brain tissues decreased (p < 0.05) in the second and the third groups as compared to the first group. The percentage of arachidonic and polyunsaturated fatty acids slightly decreased (p < 0.05) in the diabetic group in comparison to the second and third groups. The proportion of docosahexaenoic acid significantly increased (p < 0.01) in the second and third groups in contrast to the first group. The level of docosatrienoic was slightly higher (p < 0.05) in the third group than in other groups. In the liver tissues, the proportion of stearic, oleic and total monounsaturated fatty acids was slightly higher (p < 0.05) in the first group than in the other groups. The level of arachidonic, docosahexaenoic, unsaturated and total polyunsaturated fatty acid slightly increased (p < 0.05) in the second and third groups as compared to the first group, The level of myristic and stearic acids in muscle tissue slightly increased (p < 0.05) in the first group as compared to the second and third groups. The proportion of arachidonic, docosahexaenoic and unsaturated fatty acids slightly increased (p < 0.05) in the second and third groups relative to the first group. The amount of MDA was slightly higher in the diabetic group than in the other groups in all tissues. The results indicate that vitamin E supplementation, in experimental diabetes could play a role in controlling the oxidative status and altered fatty acid metabolism in tissues, thereby maintaining favourable fatty acid distribution in the tissues affected by diabetic complications, Copyright (C) 2001 John Wiley Sons, Ltd.
Keywords: diabetic rat; tissues; vitamin E; fatty acids; malondialdehyde